Pengaruh Efikasi Guru dan Kecerdasan Emosional Terhadap Pengelolaan Kelas Dimoderasi Gaya Kepemimpinan Transformasional - Asep Amaludin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2020)
This study is to examine the effect of teacher efficacy (TE), emotional intelligence (EI), on classroom management (CM) moderated by transformational leadership style (TLS) in Randudongkal District Private Vocational Schools. The research population was the Randudongkal Islamic Vocational Teachers, 7 Randudongkal Muhammadiyah Vocational Teachers, Mejagong TIO Vocational Teachers, Randudongkal 3 Vocational School Teachers in Randudongkal District, amounting to 185 people. Research data is primary data obtained directly from respondents with a questionnaire. Data analysis techniques using multiple linear regression using SPSS for Windows program. The results of the study were: teacher efficacy had no effect on classroom management, emotional intelligence had a positive and significant effect on classroom management, transformational leadership style had a positive and significant effect on classroom management.